Understanding firms' marketing and financial metric use : the impact of contemporary data - evidence from the tourism industry - Lamest, Markus (Trinity College (Dublin, Ireland). Trinity Business School, 2016)
Over several consecutive years, the accountability of the marketing function has been amongst the top research priorities of the Marketing Science Institute (MSI) and a core driver of metrics-based research. The objective of most of the metrics-based research in this domain is to establish marketing accountability through the application of marketing metrics, so that marketers are able to speak the language of key players in the finance and senior-level domain. Indeed, empirical evidence confirms that marketing accountability is one of the core drivers of marketing’s status in the firm (Verhoef and Leeflang 2009). However, managerial surveys (Carr and Schreuer 2010; McAfee and Brynjolfsson 2012), as well as evidence from case studies (Morgan, Anderson, and Mittal 2005; Wiesel, Pauwels, and Arts 2011), suggest that firms frequently struggle to establish marketing accountability. In-depth research on the actual use of marketing metrics is sparse. Recently, attention has been drawn to the challenges arising with the rapidly increasing amount of customer data available to organisations. The MSI declared the use of these data as an emerging top research priority for the period 2012- 2014. Existing research on the use of metrics was largely conducted in a time before this phenomenon began to affect businesses (e.g. Morgan, Anderson and Mittal 2005), or it uses methodologies that neglect the data-related characteristics to which firms are exposed in practice. In fact, metrics-related research agendas have often been defined by the data available to researchers, rather than the other way around (Hanssens, Rust, and Srivastava 2009). It is suggested that knowledge on the use of marketing metrics in general and attitudinal metrics in particular for the achievement of marketing accountability requires conceptual development in the context of currently available customer data. This study poses the following research question: How do firms use marketing and financial metrics in the context of contemporary data?
Keywords: Business, Ph.D.; PhD Trinity College Dublin, 2016